Production of contaminant-depleted solid recovered fuel from mixed commercial waste for co-processing in the cement industry. (15th June 2021) - Viczek, S.A.; Lorber, K.E.; Pomberger, R.; Sarc, R.
Graphical abstract: Highlights: The effects of screening, sorting, and combinations are given for 29 elements. Combining screening and NIR sorting can reduce all contaminant concentrations. Removing PVC and fine fractions causes a concentration decrease for all 29 elements. Removing black&grey materials may further reduce concentrations of Sb, Co, and Cl. Removing only PET and/or PVC can increase the concentration of certain heavy metals. Abstract: Solid recovered fuels (SRF) have increasingly substituted primary fuels in the cement industry, even up to 100%. However, contaminants originating from the discarded consumer products are transferred into waste and SRF. With increasing amounts of SRF being utilized, closely monitoring contaminant concentrations – as is already state of the art in several countries and the cement industry – is gaining importance. SRF producers may need to take measures assuring that quality criteria are met, contaminant concentrations are kept at a low level, or to produce contaminant-depleted SRF. This work investigates and discusses the potential measures to reduce contaminant concentrations: removing the fine fractions, polyethylene terephthalate (PET), polyvinyl chloride (PVC), and black&grey materials. Five streams of mixed commercial waste were coarsely comminuted, screened, PET and PVC were removed using an industrial near-infrared sorter, and black&grey materials were manually removed and further sorted by fourier-transform infrared spectroscopy. Concentrations of Ag, Al, As, Ba, Ca, Cd, Cl, Co, Cr, Cu, Fe, Hg, K, Li, Mg, Mn, Mo, Na, Ni, P, Pb, Sb, Si, Sn, Sr, Ti, V, W, and Zn in the fractions are reported, and the effect of single and combined measures is presented. Results show that black&grey materials contain significant shares of the total Sb, Cl, and Co in the waste stream. Furthermore, the concentration of several contaminants is increased when only PET and PVC is removed. Removing the fine fraction together with PVC can lead to a concentration decrease of all investigated analytes, enabling the production of a contaminant-depleted SRF.